The Influence of Service Quality and Customer Satisfaction on Customer Decisions with Customer Trust Level as a Mediation Variable at PT Gadai Mas Unit Melati - Kesogihin, Sindy Darvina; Putri, Ervina; Suma, Dewi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to analyze the effect of service quality and customer satisfaction on customer decisions with the level of customer trust as a mediating variable at PT Gadai Mas Unit Melati. This study uses a quantitative method with a purposive sampling technique, involving 80 respondents. Data collection techniques are carried out through observation and questionnaires. Data analysis methods include validity tests, reliability tests, classical assumption tests, hypothesis tests, and path analysis. The results of the study indicate that service quality (X1) partially has a significant effect on customer trust (Z) and customer decisions (Y). Customer satisfaction (X2) also has a significant partial effect on customer trust (Z) and customer decisions (Y). In addition, customer trust (Z) has a significant effect on customer decisions (Y). Simultaneous analysis shows that service quality (X1) and customer satisfaction (X2), through customer trust (Z), significantly affect customer decisions (Y). This study emphasizes the importance of adjusting services to the unique needs of customers to achieve optimal satisfaction and trust, which ultimately affects customer decisions.